2016
DOI: 10.1177/1357633x16642369
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of Internet-based physiotherapy assessment for musculoskeletal disorders: a systematic review

Abstract: Purpose The purpose of this review is to systematically explore and summarise the validity and reliability of telerehabilitation (TR)-based physiotherapy assessment for musculoskeletal disorders. Method A comprehensive systematic literature review was conducted using a number of electronic databases: PubMed, EMBASE, PsycINFO, Cochrane Library and CINAHL, published between January 2000 and May 2015. The studies examined the validity, inter- and intra-rater reliabilities of TR-based physiotherapy assessment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
158
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(172 citation statements)
references
References 49 publications
4
158
1
9
Order By: Relevance
“…reliability in the assessment of peripheral joints and the spine, with good to excellent psychometric properties for the different clinical outcomes (eg, pain, swelling, muscle strength, balance, gait, active and passive range of motion). [19][20] Lower validity and reliability have been identified in the assessment of the shoulder and elbow joints, for the examination of the nerve functioning around the elbow, the scar assessment of the knee, and the evaluation of lumbar spine posture. [19][20] Furthermore, the absence of reporting of standard error of measurement and coefficient of variation, and the involvement of assessors with different clinical expertise and training (eg, naïve, expert) may limit the generalization of findings.…”
Section: Clinical Evidence On Telerehabilitationmentioning
confidence: 99%
See 2 more Smart Citations
“…reliability in the assessment of peripheral joints and the spine, with good to excellent psychometric properties for the different clinical outcomes (eg, pain, swelling, muscle strength, balance, gait, active and passive range of motion). [19][20] Lower validity and reliability have been identified in the assessment of the shoulder and elbow joints, for the examination of the nerve functioning around the elbow, the scar assessment of the knee, and the evaluation of lumbar spine posture. [19][20] Furthermore, the absence of reporting of standard error of measurement and coefficient of variation, and the involvement of assessors with different clinical expertise and training (eg, naïve, expert) may limit the generalization of findings.…”
Section: Clinical Evidence On Telerehabilitationmentioning
confidence: 99%
“…[19][20] Lower validity and reliability have been identified in the assessment of the shoulder and elbow joints, for the examination of the nerve functioning around the elbow, the scar assessment of the knee, and the evaluation of lumbar spine posture. [19][20] Furthermore, the absence of reporting of standard error of measurement and coefficient of variation, and the involvement of assessors with different clinical expertise and training (eg, naïve, expert) may limit the generalization of findings. [19][20] On the other hand, one strength of qualitative studies investigating both patients' and physical therapists' perspectives is the good acceptability of telerehabilitation in terms of overall user experience, adherence, and satisfaction, both in MSK disorders and after elective orthopedic surgical conditions.…”
Section: Clinical Evidence On Telerehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Results also showed that the telerehabilitation assessment had excellent inter-and intra-rater reliabilities for the 6MWT, the TUGT and grip strength. These results resonate with previous research, where telerehabilitation assessments were demonstrated to be valid and reliable when compared with face-to-face assessments in other patient populations (Cox et al, 2013;Mani et al, 2017;Russell et al, 2013).…”
Section: Telerehabilitation Assessmentsupporting
confidence: 90%
“…One specialized field of tele-health is telerehabilitation, which allows the implementation of a therapeutic program via an interactive multimedia webbased platform [1], [2]. A remarkable increase in the number of patients treated by tele-rehabilitation has been noticed since the beginning of the 21 st century, especially in physiotherapy [3]. Despite the several medical and economic advantages of this new paradigm, the development of a tele-rehabilitation platform has to follow specific rules to ensure safety and efficiency.…”
Section: Introductionmentioning
confidence: 99%